Nissen fundoplication in a series of 53 consecutive patients - Тoni Ivanov Stoyanov (Journal of Biomedical & Clinical Research, 2024)
Hiatal hernia (HH) is often seen in surgery practice. The main feature of HH is the migration of abdominal viscera in the mediastinum via the esophageal hiatus. We performed - on 53 patients from November 2009 to June 2018 in the Department of General and Digestive Surgery of General Hospital of Villarobledo. Forty-one patients were diagnosed with hiatal hernia, 9 - with gastroesophageal reflux disease (GERD), and 3 - with Barrett’s esophagus. The average operative time was 89 ± 33 minutes, and the average follow-up was four years. The following complications were recorded: perforation of the distal esophagus in 1 patient (1.9%), postoperative spleen hemorrhage requiring emergency laparotomy in 1 patient (1.9%), dysphagia in 6 patients (11.3%) in the early postoperative period (treated conservatively), one patient had small bowel obstruction in the fourth postoperative year, three patients (5.6%) had radiological signs of HH recurrence and GERD despite the fundoplication. One patient (1.9%) was reoperated for stenosis of the distal esophagus and recurrent paraesophageal hiatal hernia one year after the first intervention. Postoperative ventral hernia (POVH) was seen in 2 patients (3.8%). All recurrence rate was 7.5%, recorded in 4 patients.